MAHARAH KALAM LEARNING USING THE TAQDIMUL QISHOH METHOD FROM A VYGOTSKY THEORY PERSPECTIVE AT AL-MASHDUQIAH ISLAMIC BOARDING SCHOOL AND DARUL LUGHAH WAL KAROMAH ISLAMIC BOARDING SCHOOL - Sofwan Hadianto Prasetyo; M. Faisol; Ahmad Mubaligh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the learning of maharah kalam using the Taqdimul Qissah method, from the perspective of social constructivism proposed by Lev Vygotsky, at the Al-Mashduqiah Islamic Boarding School and the Darul Lughah Wal Karomah Islamic Boarding School. This study uses a qualitative method with an evaluation study approach. Data were collected through observations and interviews with teachers and students in grade 3 at the middle school. The results of the study indicate that the taqdimul qissah method is implemented at the Al-Mashduqiah Islamic Boarding School through teacher storytelling, vocabulary explanations, comprehension discussions, and individual retelling practies. This is in accordance with Vygotsky’s principles. While at the Darul Lughah Wal Karomah Islamic Boarding School, this is implemented through storytelling, group discussions, collaborative retelling practices, and individual assignments to compose stories. The ndings indicate that learning occurs through social interaction, gradual support (scaffolding), and communication practices that encourage students to use Arabic actively. Thus, the taqdimul qishah method aligns with the learning principles outlined in Vygotsky’s theory.